2016
DOI: 10.1103/physrevx.6.031012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thickness and Interface on the Low-Temperature Enhancement of the Spin Seebeck Effect in YIG Films

Abstract: The temperature-dependent longitudinal spin Seebeck effect (LSSE) in heavy metal ðHMÞ=Y 3 Fe 5 O 12 (YIG) hybrid structures is investigated as a function of YIG film thickness, magnetic field strength, and different HM detection materials. The LSSE signal shows a large enhancement with reductions in temperature, leading to a pronounced peak at low temperatures. We find that the LSSE peak temperature strongly depends on the film thickness as well as on the magnetic field. Our result can be well explained in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
158
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(186 citation statements)
references
References 60 publications
(189 reference statements)
17
158
8
Order By: Relevance
“…Note that this also agrees with the previously reported film-thickness dependence of highmagnetic-field response of thermopower [15][16][17][18] Figure 5 and Table III are shown to discuss the power-law scaling of the temperature dependence of thermal conductivity and thermopower of all the samples. The exponent n is determined by fitting the measured data with a power-law function CT n , where C is the prefactor and T is temperature.…”
Section: Resultssupporting
confidence: 90%
“…Note that this also agrees with the previously reported film-thickness dependence of highmagnetic-field response of thermopower [15][16][17][18] Figure 5 and Table III are shown to discuss the power-law scaling of the temperature dependence of thermal conductivity and thermopower of all the samples. The exponent n is determined by fitting the measured data with a power-law function CT n , where C is the prefactor and T is temperature.…”
Section: Resultssupporting
confidence: 90%
“…While (i) is not well experimentally investigated, the existence of the µm-range length scale in the SPE [19] and the similarity between δ SPE and δ SSE suggest the dominant contribution from (ii) as in the case of the SSE [25,30]. In fact, recently, it has been demonstrated that the high magnetic fields reduce the propagation length of magnons contributing to the SSE [30].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the SSE thermopower in a Pt/YIG system was shown to be suppressed by high magnetic fields even at room temperature against the conventional theoretical expectation based on the equal contribution over the magnon spectrum [22]. This anomalously-large suppression highlights the dominant contribution of sub-thermal magnons, which possess lower energy and longer propagation length than thermal magnons [23,25,28,30]. Thus, the experimental examination of the field dependence of the SPE is an important task for understanding the SPE.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, phonon-magnon drag has been put into evidence in previous SSE experiments 8,9 , which, again, points to the importance of interactions between magnons and phonons. To the best of our knowledge, no explicit evidence for the effect of this length scale on SSE measurements has been reported to date.Previous articles on thin films using various growth techniques 10,11,12 have shown the SSE signal to increase with increasing YIG film thickness. In this study, we grow a series of 3 Pt|YIG|GGG heterostructures, with YIG thickness varying from 10 nm to 1 μm, using the same growth technique for all films.…”
mentioning
confidence: 94%
“…Previous articles on thin films using various growth techniques 10,11,12 have shown the SSE signal to increase with increasing YIG film thickness. In this study, we grow a series of 3 Pt|YIG|GGG heterostructures, with YIG thickness varying from 10 nm to 1 μm, using the same growth technique for all films.…”
mentioning
confidence: 94%